Neutralizing Antibody Correlates Analysis of Tetravalent Dengue Vaccine Efficacy Trials in Asia and Latin America. (29th November 2017) - Moodie, Zoe; Juraska, Michal; Huang, Ying; Zhuang, Yingying; Fong, Youyi; Carpp, Lindsay N; Self, Steven G; Chambonneau, Laurent; Small, Robert; Jackson, Nicholas; Noriega, Fernando; Gilbert, Peter B
Abstract : Neutralizing antibody titers postdose 3 correlate with efficacy of the CYD-TDV dengue vaccine to prevent symptomatic, virologically confirmed dengue. In 2 Phase 3 trials, high titers associated with high vaccine efficacy for all serotypes, baseline serostatus groups, and age groups. Abstract: Background: In the CYD14 and CYD15 Phase 3 trials of the CYD-TDV dengue vaccine, estimated vaccine efficacy (VE) against symptomatic, virologically confirmed dengue (VCD) occurring between months 13 and 25 was 56.5% and 60.8%, respectively. Methods: Neutralizing antibody titers to the 4 dengue serotypes in the CYD-TDV vaccine insert were measured at month 13 in a randomly sampled immunogenicity subcohort and in all VCD cases through month 25 (2848 vaccine, 1574 placebo) and studied for their association with VCD and with the level of VE to prevent VCD. Results: For each trial and serotype, vaccinees with higher month 13 titer to the serotype had significantly lower risk of VCD with that serotype (hazard ratios, 0.19–0.43 per 10-fold increase). Moreover, for each trial, vaccinees with higher month 13 average titer to the 4 serotypes had significantly higher VE against VCD of any serotype ( P < .001). Conclusions: Neutralizing antibody titers postdose 3 correlate with CYD-TDV VE to prevent dengue. High titers associate with high VE for all serotypes, baseline serostatus groups, age groups, and both trials. However, lowest titers do not fully correspond to zero VE, indicating that other factors influence VE.